1989
DOI: 10.2170/jjphysiol.39.497
|View full text |Cite
|
Sign up to set email alerts
|

Specific mitochondrial responses to running training are induced in each type of rat single muscle fibers.

Abstract: The effects of training by running (sprint or endurance) on the mitochondrial volume, number, and succinate dehydrogenase (SDH) activity of different types of single muscle fibers, and on the elemental composition of soleus and extensor digitorum longus muscles were studied employing histochemical, electron microscopic, and electron probe-micro analysis (EPMA). Newly weaned male Wistar rats were trained on a motor-driven treadmill endurance exercise for 14 weeks. The relative mitochondrial volume per single mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 35 publications
0
5
1
Order By: Relevance
“…The proportion of type IIa (fast-twitch fi ber with high oxidative capacity) in the R portion of SM muscle was signifi cantly (p < 0.01) decreased by the resection of STG tendons, while there were no signifi cant diff erences in type I (slow-twitch fi ber) and IIb (fast-twitch fi ber with low oxidative capacity) in the R portion of SM muscle. These changes in fi ber type compositions were not consistent with previous studies using other experimental models, such as muscle training [4,36,38] , tenotomy [43] , hypergravity [26] , denervation [29] , inactivity [47] , etc. Therefore, the transformation of fi ber type composition in the present study could not provide a type or kind of stimulus induced by the resection of STG tendons.…”
Section: Discussion ▼contrasting
confidence: 89%
See 1 more Smart Citation
“…The proportion of type IIa (fast-twitch fi ber with high oxidative capacity) in the R portion of SM muscle was signifi cantly (p < 0.01) decreased by the resection of STG tendons, while there were no signifi cant diff erences in type I (slow-twitch fi ber) and IIb (fast-twitch fi ber with low oxidative capacity) in the R portion of SM muscle. These changes in fi ber type compositions were not consistent with previous studies using other experimental models, such as muscle training [4,36,38] , tenotomy [43] , hypergravity [26] , denervation [29] , inactivity [47] , etc. Therefore, the transformation of fi ber type composition in the present study could not provide a type or kind of stimulus induced by the resection of STG tendons.…”
Section: Discussion ▼contrasting
confidence: 89%
“…It has been well documented that an increase in mitochondrial volume has been observed in exercise-trained skeletal muscles [44] . It has been also suggested that the responses in the mitochondrial volume to exercise-induced loading diff er according to the types of muscle fi bers [38] . Therefore, the increased mitochondrial volume might be derived from the increased demand of oxidative energy metabolism [35] as a compensational phenomenon following the resection of STG.…”
Section: Discussion ▼mentioning
confidence: 99%
“…Using the Krogh model (incorporating the capillary supply), the critical capillary PO2 did not change in the deep region, whereas it increased by 25% in the superficial region. tissue (71), indicates that atrophy is accompanied by a proportional loss of mitochondria in the deep region. The increased integrated SDH activity in the superficial region, on the other hand, indicates that although atrophy also occurred in this region, mitochondrial biogenesis was elevated.…”
Section: Region-specific Adaptation In Oxidative Capacitymentioning
confidence: 99%
“…Our data suggest that lipid peroxidation is, at least partially, associated with the protein oxidative modification during physical activity with pre-conditioned runners. Since regular exercise increases the number and activity of mitochondria in muscles [15], pre-conditioned runners may have more mitochondria to produce free radicals to modify proteins. The protein 3-NT level was not significantly altered in the plasma of the marathon runners.…”
Section: Discussionmentioning
confidence: 99%